Indole diketopiperazine alkaloids from the deep-sea-derived fungus Aspergillus sp. FS445. Issue 20 (13th October 2022) - Liu, Zhaoming; Chen, Yuchan; Li, Saini; Hu, Caiyun; Liu, Hongxin; Zhang, Weimin
Abstract: Twelve indole diketopiperazine alkaloids (1 ‒12 ) including four new ones aspechinulins A‒D (1, 3, 5 and 12 ) were isolated from the deep-sea-derived fungus Aspergillus sp. FS445. Their structures were elucidated through spectroscopic analysis and the absolute configurations were determined by analyzing the experimental ECD data as well as the quantum chemical calculations. Compounds 1, 3 and 5 represented the first examples of indole diketopiperazine derivatives constructing a C5 unit at 11-NH through an imide linkage. The NO production inhibitory activity of the isolated compounds was evaluated and compounds 2 ‒5, 7 and 9 exhibited potential inhibitory activities against NO production with the IC50 values in the range of 20 ∼ 90 µM.